Impact listening - Kisslinger, Ellen (Longman Asia ELT, 2001)
Impact listening is an exciting series that features an abundance of rich input and a variety of creative activities. The series helps students develop listening for social academic and business purposes. Each level features 15 thematic units plus 3 review units using an effective 4 step approach to teaching listening: warm up, listening task, real world listening and interaction link